Restructuring and Introduction of Competition in the Infrastructure Industries - Jankauskas, Vidmantas (Ekonomika, 2000)
Infrastructure industries (energy sector, telecommunications, transport) for a long time were treated as natural monopolies, mostly owned and regulated by the Government. Recent development, in many countries around the world: deregulation, restructuring and privatisation of the infrastructure industries have shown posibilities to separate competitive and monopoly segment, of these industries and introduce competition as also private ownership in the competitive activities. For example, electricity sector was restructured into generation, transmission, distribution and supply activities, and competition as also private capital were introduced in generation and supply of electricity. Lithuanian infrastructure industries were vertically inttegrated state owned (or with some minor private capital share) monopolies until 2000, despite many plans, projects and promises to restructure these industries. Only now, in the year 2000, the Goverment launched a plan to restructure electricity, gas and railway industries and attract some private investments. The article deals with the analysis of the recent development, in restructuring of the infrastructure industries abroad, it analyses various plans for the restructuring of the Lithuanian electricity. gas and other monopolies and touches some possible future developments.